The effectiveness of a training program in developing expressive and receptive language skills and social interaction among students of learning disabilities in Ajloun schools - AL- qwaqneh, Bara Azzam Ali (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the effectiveness of a training program to develop the skills of expressive language and receptivity and social interaction among a sample of students with learning disabilities in Ajloun schools. The study sample consisted of (20) students with difficulties from the sixth grade who were deliberately selected from Ajloun Elementary School for Boys. To an experimental and control group, the researcher applied the two tools before and after the control and experimental groups. The results of the study showed that there are statistically significant differences on all dimensions of expressive and receptive language skills and social interaction skills in the pre and post measurements in the performance of students with learning disabilities in the experimental and control groups attributed to the training program used in the study, for the benefit of students with learning disabilities in the experimental group. I learned expressive language skills, receptivity and social interaction through the program sessions. The study reached a number of recommendations and research proposals, most notably: the preparation of other therapeutic language programs targeting all types of language disorders in primary school students, and provide planners, infectious and implementers of learning disabilities programs with language and social skills and appropriate educational activities. Conduct .studies highlighting other age groups among students with language disorders